Physico-Chemical Characteristics of Gleyic Luvisols and Gleyic Listosols Production Areas of Garden Produce in Nieki Valley, South-East of Côte D’ivoire - Nantarie , Toure; Patrice, Kouadio Koffi; Eric, Kwadjo Koffi; Albert, Yao-Kouame (Asian Journal of Agriculture and Rural Development, 2015)
A study of the physico chemical properties of gleyic Luvisols and gleyic Histosols was carried on in Nieki Valley, a vegetable crops production area in South-East of Côte d’Ivoire. Soil samples were collected at different depths (0-15 cm and 15-40 cm) on each of the sites studied for laboratory analysis. The results obtained of physical analysis show that the texture of soil is generally less thin and essentially provided in heavy clays. The observed average values of the index of crusting and the ability to cracking show that soils are not crusting and have an excellent ability to cracking. The results of physical analysis also show that the soils have an index of structural stability that change from very stable to stable and a very high risk of asphyxiation. Results of chemical analysis reveal that the pH values increased with soil depth and are higher in field soils than in control soils. Moreover, organic matter in soils studied is more abundant in surface horizons and decreases with depth. However, the contents of calcium, magnesium and potassium are lower in the surface horizons and increase with depth.